NERDD: a web portal providing access to in silico tools for drug discovery - Stork, Conrad; Embruch, Gerd; Šícho, Martin; de Bruyn Kops, Christina; Chen, Ya; Svozil, Daniel; Kirchmair, Johannes (Bioinformatics (Oxford, England), 2020)
SUMMARY: The New E-Resource for Drug Discovery (NERDD) is a quickly expanding web portal focused on the provision of peer-reviewed in silico tools for drug discovery. NERDD currently hosts tools for predicting the sites of metabolism (FAME) and metabolites (GLORY) of small organic molecules, for flagging compounds that are likely to interfere with biological assays (Hit Dexter), and for identifying natural products and natural product derivatives in large compound collections (NP-Scout). Several additional models and components are currently in development. AVAILABILITY AND IMPLEMENTATION: The NERDD web server is available at https://nerdd.zbh.uni-hamburg.de. Most tools are also available as software packages for local installation.
Keywords: Computers; Computer Simulation; Drug Discovery; počítačová simulace; software; internet; biologické přípravky; objevování léků; Software; Biological Products; počítače; Internet